2019
DOI: 10.1186/s13063-019-3868-4
|View full text |Cite
|
Sign up to set email alerts
|

Reporting quality and adherence of randomized controlled trials about statins and/or fibrates for diabetic retinopathy to the CONSORT checklist

Abstract: BackgroundA considerable amount of randomized controlled trials (RCTs) have been published on statins and/or fibrates for diabetic retinopathy, a clinical condition associated with high social and economic burden. Adherence to the CONSORT statement items is imperative to ensure transparency and reproducibility in clinical research. The aim of this study is to assess the reporting quality and the adherence to CONSORT of RCTs assessing statins and/or fibrates for diabetic retinopathy.MethodsWe conducted a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Other studies in the medical literature have also shown a high prevalence of non-adherence to the CONSORT guidelines in RCT abstracts 60 , 61 , 62 , 63 , 64 , 65 . For example, Mozetic et al found that the most underreported items were related to the methods items of CONSORT, such as trial design, allocation concealment, implementation of randomization sequence, and blinding [63] . Gallo et al also found this, with limited adherence to the CONSORT for abstracts checklists among RCT abstracts published in the top plastic surgery journals [64] .…”
Section: Discussionmentioning
confidence: 87%
“…Other studies in the medical literature have also shown a high prevalence of non-adherence to the CONSORT guidelines in RCT abstracts 60 , 61 , 62 , 63 , 64 , 65 . For example, Mozetic et al found that the most underreported items were related to the methods items of CONSORT, such as trial design, allocation concealment, implementation of randomization sequence, and blinding [63] . Gallo et al also found this, with limited adherence to the CONSORT for abstracts checklists among RCT abstracts published in the top plastic surgery journals [64] .…”
Section: Discussionmentioning
confidence: 87%
“…A search for a safer systemic approach to preventing or delaying development of complications has re-examined the benefits of the lipid-lowering drug fenofibrate ( 223 , 224 ), but the, albeit uncommon, side-effects have also prevented its widespread use. Experience with the liberally prescribed statins has also been examined as a possible means of eliminating the hyperlipidemic risk factor for DR, and there is some evidence from RCT’s ( 225 227 ) but a critical analysis of published data suggests that the quality and reporting of the data may be flawed ( 228 ). Experimentally, rosuvastatin has been shown to inhibit leukostasis in which the effect appeared to act on the endothelium rather than the leukocytes, thus pointing to a primary metabolic defect in the endothelium initiating leukostasis ( 145 ).…”
Section: Preventing and Treating The Microvasculopathy Of Obesity/thementioning
confidence: 99%
“…This study aimed to show how the resulting bias and other dubious presentations of outcomes can appear in RCT on DR and alert readers to read the articles with more criteria. Many of these biases have already been reported in the literature 32 and could be corrected with strict compliance with CONSORT rules. 17 We observed the persistence of a lack of standardization in assessing outcomes, which makes it challenging to carry out systematic reviews.…”
Section: Lack Of Relevance To Patients and Decision-makers Occurs When The Laboratory Markers Do Not Presentmentioning
confidence: 90%